Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1021/ie9802111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shear Stress within the Spinneret on Hollow Fiber Membrane Morphology and Separation Performance

Abstract: The effects of shear stress and shear experience within a spinneret during hollow fiber spinning on membrane morphology, gas separation performance, and thermal and mechanical properties have been experimentally determined. We purposely spun the hollow fibers using a wet phase inversion process and water as the external coagulant with the belief that the effect of gravity (elongational stress) on fiber formation can be significantly reduced and the orientation induced by shear stress within the spinneret can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Therefore, both procedures for membrane preparation in addition to membrane material characteristics are of great importance for improving performance of gas separation membranes. The influence of shear rate on the morphology and separation performance of hollow fiber membranes was first studied by Chung et al [23].…”
Section: Air Separationmentioning
confidence: 99%
“…Therefore, both procedures for membrane preparation in addition to membrane material characteristics are of great importance for improving performance of gas separation membranes. The influence of shear rate on the morphology and separation performance of hollow fiber membranes was first studied by Chung et al [23].…”
Section: Air Separationmentioning
confidence: 99%
“…Aptel et al 13 found that increasing the dope extrusion rate could reduce the permeability. Chung et al [14][15][16] have also investigated the effect of the shear stress and shear rate within the spinneret on the morphology and properties of the hollow fiber membranes. Their results revealed that the fibers had a lower permeability due to the greater molecular orientation but a higher selectivity with increasing shear rates.…”
Section: Introductionmentioning
confidence: 99%
“…25 This technique has been employed to qualitatively characterize the degree of fiber molecular orientation for hollow fiber membranes. 18,26,27 Generally, a high CTE indicates disoriented molecular chains, whereas a minimum CTE means highly orientated molecular chains. Initially, fibers spun with high shear rates show a lower CTE value compared to those spun with low shear rates due to the enhanced orientation and alignment in the polymer chains (Table VI).…”
Section: The Effect Of Shear Rates On Thermal Mechanical Propertiesmentioning
confidence: 99%